The future of global organizing - Tulder, Rob van; Verbeke, Alain; Drogendijk, Rian (Emerald, 2015)
This latest volume of Progress in international business research explores novel ways in which international business is organized. Contributions advance our understanding and stretch our thinking about new organizational and geographic structures in MNCs, and other organizational forms across borders and geographies. Authors ask challenging questions: will the traditional MNC as we know it be replaced by other dominant designs, and what new forms of global organizing can we expect in the future? What do contemporary digital and technological developments, e.g. social media, virtual worlds, and cloud services, imply for the international organization of work, communication, and management practices?
Keywords: International business enterprises -- Management.; Competition, International.; Globalization -- Economic aspects.; elektronické knihy; electronic books